The differences in learning motivation of college freshmen in Northwest China - Qiao, Ke; Xu, Ruizhao; Liu, Bailong; Chen, Xiangyang; Gu, Pan (Frontiers in Psychology, 2022)
The study aimed to investigate the learning motivation of freshmen of the university in Northwest China, which can supply a reference for improving their learning quality and objectives. The data were collected from 800 freshmen studied in different majors with learning motivation questionnaire, and analyzed by principal component analysis method. The differences of learning motivation between different majors, genders, regions students are studied. The results show that gender, seeking knowledge orientation and material pursuit have significant effects on students' learning motivation. The individual achievement has obvious differences in gender (P = 0.001 < 0.05), and material pursuit has obvious differences in whether it is an only child or not, while other factors on the gender, regional, and whether the one-child had no obvious difference. According to the results of research, the measures to improve learning motivation are proposed. Our research results provide a method and basis for quantifying students' learning motivation.